Carbon and Nitrogen Uptake of Calcareous Benthic Foraminifera along a Depth-Related Oxygen Gradient in the OMZ of the Arabian Sea - Enge, Annekatrin J.; Wukovits, Julia; Wanek, Wolfgang; Watzka, Margarete; Witte, Ursula F. M.; Hunter, William R.; Heinz, Petra (Frontiers in Microbiology, 2016)
Foraminifera are an important faunal element of the benthos in oxygen-depleted settings such as Oxygen Minimum Zones (OMZs) where they can play a relevant role in the processing of phytodetritus. We investigated the uptake of phytodetritus (labeled with 13C and 15N) by cal-careous foraminifera in the 0-1 cm sediment horizon under different oxygen concentrations within the OMZ in the eastern Arabian Sea. The in situ tracer experiments were carried out along a depth transect on the Indian margin over a period of 4 to 10 days. The uptake of phy-todetrital carbon within 4 days by all investigated species shows that phytodetritus is a rele-vant food source for foraminifera in OMZ sediments. The decrease of total carbon uptake from 540 to 1100 m suggests a higher demand for carbon by species in the low-oxygen core region of the OMZ or less food competition with macrofauna. Especially Uvigerinids showed high uptake of phytodetrital carbon at the lowest oxygenated site. Variation in the ratio of phytodetrital carbon to nitrogen between species and sites indicates that foraminiferal carbon and nitrogen use can be decoupled and different nutritional demands are found between spe-cies. Lower ratio of phytodetrital carbon and nitrogen at 540 m could hint for greater demand or storage of food-based nitrogen, ingestion or hosting of bacteria under almost anoxic condi-tions. Shifts in the foraminiferal assemblage structure (controlled by oxygen or food availabil-ity) and in the presence of other benthic organisms account for observed changes in the pro-cessing of phytodetritus in the different OMZ habitats. Foraminifera dominate the short-term processing of phytodetritus in the OMZ core but are less important in the lower OMZ bounda-ry region of the Indian margin as biological interactions and species distribution of foraminif-era change with depth and oxygen levels.